2010
DOI: 10.1007/s11064-010-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Protective Effects of Tripterygium regelii Extract on Hydrogen Peroxide-Induced Injury in Human Dopaminergic Cells, SH-SY5Y

Abstract: The present work was conducted to investigate the antioxidant activity and neuroprotective effects of Tripterygium regelii extract (TRE) on H(2)O(2)-induced apoptosis in human dopaminergic cells, SH-SY5Y. TRE possessed considerable amounts of phenolics (282.73 mg tannic acid equivalents/g of extract) and flavonoids (101.43 mg naringin equivalents/g of extract). IC(50) values for reducing power and DPPH radical scavenging activity were 52.51 and 47.83 microg, respectively. The H(2)O(2) scavenging capacity of TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Park et al (2010) reported that rosmarinus extract significantly attenuated the H 2 O 2 -induced downregulation of TH, and AADC gene in SH-SY5Y cells. Choi et al (2010) reported an increased expression of TH and BDNF genes on pretreatment with T. regelii extract accounting for its neuroprotective actions. Sapkota et al (2011) reported detoxified extract of R. verniciflua prevented the downregulation of BDNF and TH against rotenone-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al (2010) reported that rosmarinus extract significantly attenuated the H 2 O 2 -induced downregulation of TH, and AADC gene in SH-SY5Y cells. Choi et al (2010) reported an increased expression of TH and BDNF genes on pretreatment with T. regelii extract accounting for its neuroprotective actions. Sapkota et al (2011) reported detoxified extract of R. verniciflua prevented the downregulation of BDNF and TH against rotenone-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Many plant species in diverse regions of the world have been screened for their neuroprotective activity. Extracts of plants such as Green tea (Cho et al 2008), Tripterygium regelii (Choi et al 2010), Rhus verniciflua (Sapkota et al 2011), Eucommia ulmoides (Kwon et al 2012), Hyptis suaveolens (Ghaffari et al 2014), Bacopa monnieri (Thomas et al 2013), and Cyperus rotundus ) were reported to possess antioxidant properties and neuroprotective effects. However, there are very few reports on the neuroprotective compounds of fungal origin.…”
Section: Introductionmentioning
confidence: 99%
“…2A, a-g). In a previous study, Zhang et al (2008) (Lin et al 2009;Choi et al 2010). In an earlier study, Sunil et al (2011) has proven that total oligomeric flavonoids of Cyperus extract ameliorate the symptoms of ischemic-reperfusion injury in rats by improving the antioxidant status.…”
Section: Tpc and Flavonoid Contentsmentioning
confidence: 96%
“…The reaction was performed in 20-ll reaction volume using 10 pmol of the following primers-brain derived nerve growth factor (BDNF), F:5 0 -GAT GAC CAT CCT TTT CCT TAC TAT GG-3 0 R:5 0 -CTA TCT TCC CCT TTT AAT GGT CAA T-3 0 ; b-actin, F:5 0 -CCT CTA TGC CAA CAC AGT-3 0 R:5 0 -AGC CAC CAA TCC ACA CAG-3 0 (Choi et al 2010). The PCR conditions were-denaturation at 94°C for 30 s, annealing at 55.8°C for BDNF and at 56°C for b-actin, and polymerization at 72°C for 30 s. The cyclic process was performed 35 times for BDNF and 30 times for b-actin.…”
Section: Polymerase Chain Reaction (Pcr) and Product Analysismentioning
confidence: 99%
“…ROS leading to a radical reaction chain which degrades organic molecules vital to know the DNA, lipids and proteins in the body, which have been implicated in the etiology and pathophysiology [4,5] .In recent years increased interest is observed on the biological effects of natural antioxidant included in the fight against oxidative stress involved in the initiation and progression of several diseases. In addition, many of the phenolic compounds have been shown to contain high levels of antioxidant and antimicrobial activities [6] .The aim of this study consisted to valorization of medicinal and aromatic plants of the Algeria flora, in order to evaluate the total polyphenols contents and the antioxidant activity of extracts of Z. album and A. scoparium, tow Algerian Sahara plants used in various folk medicines.…”
Section: Introductionmentioning
confidence: 99%